Influence of instructional resources in learning agriculture in secondary school on employment creation in Vihiga County, Kenya - Aholi, Seraphine Sherry; Konyango, Jacob J. J. Ochieng’; Kibett, Joash K. (My University, 2018)
The purpose of this study was to determine the influence of instructional resources in learning agriculture in secondary sch ool on employment creation in Vihiga County, Kenya. The study was conducted in Emuhaya Constituency, and it adopted qualitative research design using descriptive survey method. The target population was the youth who learnt agriculture in secondary schools . The study purposively sampled 150 youth out of total population of 2,736 youth who sat for Kenya Certificate of Secondary Education (KCSE) in Emuhaya Constituency between 2010 to 2012. Data were collected using structured questionnaire. The instrument wa s validated by Academic experts from the Department of Agricultural Education and Extension. The instrument had Cronbach’s Alpha reliability coefficient of 0.814. The data was analyzed using the Statistical Package for Social Sciences, version 20, based on the objectives and research questions. The relationship between the secondary school Instructional resources and employment creation was tested using Pearson Correlation. Frequency tables and percentages summarized the results. The study established that teaching agriculture in secondary school using agricultural instructional resources was positively related to employment creation for out of school youth in Emuhaya Constituency of Vihiga County. The study recommended formulation of policies that promote h armonization between teaching agriculture and employment creation. It recommended youth to take up agricultural activities for employment, and recommended replication of similar studies in other levels of education such as primary and university.
Keywords: Agricultural policy; Employment creation; Learning resources; Students attitude; Agricultural education.